Symptomatic rib fracture nonunion: a systematic review of the literature - DeGenova, Daniel T.; Peabody, John T.; Schrock, John B.; Homan, Morgan D.; Peguero, Emil Suriel; Taylor, Benjamin C. (Archives of orthopaedic and trauma surgery, 2024)
Introduction Rib fractures commonly occur in trauma patients with varying presentations. Though the literature in recent years has moved toward favoring more early intervention of acute rib fractures, little has been reported on the matter of surgical fixation for symptomatic rib fracture nonunions. Materials and methods We performed a review of PubMed and Cochrane databases for articles published since 2000. Inclusion criteria were studies with greater than six months of follow-up, while case studies were excluded. A thorough analysis was performed on patient outcomes, complications reported, operative techniques utilized, and fixation systems used, among other parameters reported by the articles. Results One hundred and thirty-nine studies resulted from our review, and a total of nine studies met our inclusion criteria with a combined total of 182 patients who underwent open reduction and internal fixation for symptomatic rib fracture nonunions. All studies reported a significant reduction of pain with increased satisfaction in the majority of patients. There were a total of 71 postoperative complications, the most common of which included surgical site infections, hardware failure, and hematoma. The most serious complications were insulting injury to the lung parenchyma or pleura; however, these were extremely rare based off the current literature. The use of bone grafting was common with eight of the nine studies mentioning the benefits of grafting. Conclusion Surgical stabilization of rib fracture nonunions appears to be an appropriate treatment alternative, and various techniques and approaches may be used with similar success. Further studies with higher level of evidence are recommended on the subject.